Child Custody Rights Resulting from Divorce of Inter-Religious Families from A Legal Perspective Islam: Hak Asuh Anak Akibat Perceraian Beda Agama dalam Persfektif Hukum Islam - Kamila Nuratika Hasyim; Yusup Hidayat (Yapilin Press, 2026)
Child custody remains one of the most contested issues in interfaith divorce cases, with polygamy frequently cited as a contributing factor to marital breakdown. These circumstances often result in legal disputes, particularly regarding which party holds the dominant legal authority in custodial matters. This research aims to explore the regulation of child custody in interreligious divorce from the perspectives of Islamic jurisprudence and Indonesian positive the research utilizes an integrative methodology that combines normative legal analysis with empirical investigation, utilizing document analysis from several judicial rulings. Legal references include Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law (KHI), and selected fatwas formulated and declared by the Indonesian Council of Ulama (MUI). analysis draws upon the theory of maslahah (public benefit), justice theory, and the principle of child rights protection. Findings suggest that, in Islamic law, custody of non-mummayiz children (under 12 years of age) is generally granted to the mother, unless disqualified due to specific circumstances such as religious conversion. Conversely, Indonesian national law prioritizes the